ENERGY QUALITY OF WOOD AND CHARCOAL FROM Eucalyptus spp. STORED OUTDOORS - Ferreira Saraiva, Karolayne; Marchesan, Raquel; Barista Martins, Joyce; Pereira Eufrazio de Moraes, Thatiele; Gomes Colares, Carla Jovania; Bezerra de Souza, Priscila (Floresta, 2025)
The objective of this study was to evaluate the behavior of Eucalyptus spp. wood stored outdoors over a period of four months, focusing on the energy quality of the wood and charcoal. During the four months, samples were collected each month to analyze the wood and charcoal. The analyses included the assessment of the physical, chemical, and energetic properties of the wood, as well as the properties of the charcoal. During storage, the wood exhibited mass losses (0.22 to 1.39%) and basic density (0.75 to 0.64 g/cm³) in all treatment months; however, until the third month, there was an increase in total lignin content due to losses in holocellulose. Despite the losses in mass and holocellulose, there was an increase in energy for the wood. For the charcoal, there was an increase in fixed carbon and calorific value until the third month. It is concluded that until the third month of treatment, the wood showed positive performance for energy generation. In contrast, in the fourth month, it exhibited lower basic and apparent density, carbon stock, and energy density, resulting in decreased energy potential. The recommendation from this study is that Eucalyptus spp. wood demonstrated good resistance to outdoor storage with good quality for up to three months; beyond that, it began to show significant losses.